Creatividad verbal y estrategias metacognitivas: un estudio correlacional en estudiantes de primaria y secundaria - Falconí Ramat, Bárbara (2024)
The present research aimed to demonstrate the correlation between verbal creativity and metacognitive strategies in sixth-grade primary and first-grade secondary students from a private school in Metropolitan Lima. For this purpose, 92 participants were evaluated (58 from sixth grade primary and 34 from first grade secondary). The Torrance Tests of Creative Thinking (TTCT), the Metacognitive Strategies Inventory, and the Self-Report of Perceived Verbal Creativity and Frequency of Creative Activities were used. The instruments underwent the corresponding adaptation and validation processes. A significant, although of low magnitude, correlation was found between Verbal Creativity and Metacognitive Strategies, as well as between the metacognition factor Comprehension Monitoring and Verbal Creativity. Similarly, a highly significant, though also low, correlation was found between the metacognition factor Information Management and Verbal Creativity. Furthermore, participants with high and low scores in Verbal Creativity obtained high and low scores in Metacognitive Strategies, respectively, with a highly significant correlation in the metacognition factor Information Management and a significant correlation in Comprehension Monitoring. Finally, a nearly significant result was found between participants with high and low scores in Self-Perception of Verbal Creativity and Verbal Creativity.